Ways of worship - Chopra, Radhika (Haryana, India Panguin Pendom House, 2020)
ways of worship cover specific religious practices (like Hinduism's Vedas, Judaism's Torah) or broader spiritual guides, with examples like Radhika Chopra's Ways of Worship (visualizing Indian rituals) or Christian books like Worship Matters, focusing on devotional practices, scripture, music, and daily spiritual disciplines for connecting with the divine, from ancient texts to modern interpretations.